2006
DOI: 10.1093/jb/mvj095
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient RNA Aptamer against Human Influenza B Virus Hemagglutinin

Abstract: Aptamers are known for their higher discriminating ability between closely related molecules and their requirement for only a small region for binding, as compared to an antibody. In the present studies, we have isolated a specific RNA aptamer against the influenza virus B/Johannesburg/05/1999 by an in vitro selection procedure. The aptamer bound efficiently to the HA of influenza B and required 5 mM MgCl(2) ion for its recognition. The aptamer not only distinguished HA derived from the influenza A virus, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 24 publications
0
71
0
Order By: Relevance
“…The potential for small RNAs to act as protein agonists has long been appreciated, as demonstrated by the directed evolution of RNA aptamers that inhibit HIV reverse transcriptase (26) and influenza virus B hemagglutinin (27), among others (28). Despite the successful experimental generation of these artificial species, there are very few examples of naturally occurring RNAs that act directly to impede protein activity in vivo, and ToxI antitoxins are, to our knowledge, the only RNAs whose function is to inhibit their own parent-processing enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for small RNAs to act as protein agonists has long been appreciated, as demonstrated by the directed evolution of RNA aptamers that inhibit HIV reverse transcriptase (26) and influenza virus B hemagglutinin (27), among others (28). Despite the successful experimental generation of these artificial species, there are very few examples of naturally occurring RNAs that act directly to impede protein activity in vivo, and ToxI antitoxins are, to our knowledge, the only RNAs whose function is to inhibit their own parent-processing enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…After the RNA was incubated with the target protein at room temperature for 10 min, the protein-RNA complexes were filtered through a prewetted nitrocellulose acetate filter (HAWP filter, 0.45 m and 13.0 mm; Millipore) fitted in a "pop-top" filter holder (Nuclepore) and washed with 1 ml binding buffer. The RNAs that were retained on the filter were eluted and recovered as previously described (14,15). The recovered RNAs were reverse transcribed in 20 l of a reaction mixture containing 50 mM Tris-HCl (pH 8.0), 40 mM KCl, 6 mM MgCl 2 , 0.4 mM deoxynucleoside triphosphates (dNTPs), 2.5 M primer, and 5 U avian myoblastosis virus (AMV) reverse transcriptase (Seikagaku).…”
Section: Viral Proteinsmentioning
confidence: 99%
“…32 P]ATP, and binding studies were performed by using a filter binding assay similar to that previously reported (15,21,22). The binding and in vitro transcription conditions were similar to those used for selection, except for the RNA and gD protein concentrations.…”
Section: Viral Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another separate report, the same group has also utilized the same selection approach to generate RNA aptamers against the HA of human influenza B (a total of 9 selection cycles performed). [15] Among the obtained sequences, one of the aptamer was observed to demonstrate high selectivity as it is able to differentiate between the HA from influenza A and B viruses. Again via SPR, its K d was measured to be ~720 pM and, similar to human influenza A, the generated RNA aptamer is observed to be able to inhibit HA-mediated membrane fusion process for human influenza B.…”
Section: Bacillus Anthracis Spores (Cat-a Pathogen)mentioning
confidence: 99%